Raised serum Interleukin‐6 identifies patients with liver cirrhosis at high risk for overt hepatic encephalopathy. Issue 10 (3rd October 2019) - Labenz, Christian; Toenges, Gerrit; Huber, Yvonne; Nagel, Michael; Marquardt, Jens U.; Schattenberg, Jörn M.; Galle, Peter R.; Labenz, Joachim; Wörns, Marcus‐Alexander
Summary: Background: Systemic inflammation is a driving force for the development of hepatic encephalopathy and recent studies demonstrated that elevated Interleukin‐6 (IL‐6) serum levels are associated with the presence of minimal hepatic encephalopathy in patients with liver cirrhosis. Aim: To test the hypothesis that IL‐6 is a suitable marker to identify patients with liver cirrhosis at high risk for the development of overt hepatic encephalopathy. Methods: 201 patients were included into this prospective cohort study and were followed for a mean time of 322 days. Covert hepatic encephalopathy was diagnosed according to the West‐Haven criteria (hepatic encephalopathy grade 1) and with the portosystemic encephalopathy (PSE) test. Results: The cumulative incidence of overt hepatic encephalopathy was higher in patients with IL‐6 levels above the median of 9 pg/mL than in patients with IL‐6 levels at or below the median (35.6% vs 1.9%, P < .001). After adjustment for covert hepatic encephalopathy, history of overt hepatic encephalopathy, C‐reactive protein (CRP) and model for end‐stage liver disease (MELD), IL‐6 levels above the median remained independently associated with the development of overt hepatic encephalopathy. The predictive performance of IL‐6 regarding the development of overt hepatic encephalopathy during the next 180 days (AUROC, 0.931) was numerically higher than that of MELD (AUROC, 0.841) or CRP (AUROC, 0.835). In patients without prior overt hepatic encephalopathy, the predictive performance of IL‐6 (AUROC, 0.966) was even significantly higher than that of MELD (AUROC 0.843) or CRP (AUROC 0.850). The ideal cut‐off for IL‐6 in this setting was 23.5 pg/mL with a sensitivity and specificity of 89.3% and 89.5% respectively. Conclusion: IL‐6 serum levels are closely linked to the development of overt hepatic encephalopathy in patients with liver cirrhosis.